Beta cells deficient for Renalase counteract autoimmunity by shaping natural killer cell activity - Bode, Kevin; Wei, Siying; Gruber, Isabella; Li, Jian; Kissler, Stephan; Yi, Peng (Frontiers in Immunology, 2024)
Type 1 diabetes (T1D) arises from autoimmune-mediated destruction of insulin-producing pancreatic beta cells. Recent advancements in the technology of generating pancreatic beta cells from human pluripotent stem cells (SC-beta cells) have facilitated the exploration of cell replacement therapies for treating T1D.However, the persistent threat of autoimmunity poses a significant challenge to the survival of transplanted SC-beta cells. Genetic engineering is a promising approach to enhance immune resistance of beta cells as we previously showed by inactivating of the Renalase (Rnls) gene. Here we demonstrate that Rnls loss-offunction in beta cells shape autoimmunity by mediating a regulatory Natural Killer (NK) cell phenotype important for the induction of tolerogenic antigen presenting cells. Rnls-deficient beta cells mediate cellcell contact-independent induction of hallmark anti-inflammatory cytokine Tgfβ1 in NK cells. In addition, surface expression of regulatory NK immune checkpoints CD47 and Ceacam1 are markedly elevated on beta cells deficient for Rnls. Altered glucose metabolism in Rnls mutant beta cells is involved in upregulation of CD47 surface expression. These findings are crucial to a better understand how genetically engineered beta cells shape autoimmunity giving valuable insights for future therapeutic advancements to treat and cure T1D. Datasets from our scRNAseq experiments are available from the Gene Expression Omnibus (https://www.ncbi.nlm.nih.gov/geo/) under accession number GSE226361 as described before 10 .